2007
DOI: 10.1007/s11104-007-9193-9
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of manure, charcoal and mineral fertilization on crop production and fertility on a highly weathered Central Amazonian upland soil

Abstract: Application of organic fertilizers and charcoal increase nutrient stocks in the rooting zone of crops, reduce nutrient leaching and thus improve crop production on acid and highly weathered tropical soils. In a Weld trial near Manaus (Brazil) 15 diVerent amendment combinations based on equal amounts of carbon (C) applied through chicken manure (CM), compost, charcoal, and forest litter were tested during four cropping cycles with rice (Oryza sativa L.) and sorghum (Sorghum bicolor L.) in Wve replicates. CM ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
575
4
31

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,101 publications
(691 citation statements)
references
References 34 publications
47
575
4
31
Order By: Relevance
“…Results from our previous long-term monitoring suggest that swine manure and mineral fertilizer may increase soil acidity (Dong et al, 2012), which is in agreement with Steiner et al (2007). The positive relationships between soil pH and TP contents in this study confirmed that calcium-magnesium phosphate fertilizers could neutralize acidity in acid soils (Fig.…”
Section: Effects Of Fertilizer Practices On Soil Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…Results from our previous long-term monitoring suggest that swine manure and mineral fertilizer may increase soil acidity (Dong et al, 2012), which is in agreement with Steiner et al (2007). The positive relationships between soil pH and TP contents in this study confirmed that calcium-magnesium phosphate fertilizers could neutralize acidity in acid soils (Fig.…”
Section: Effects Of Fertilizer Practices On Soil Propertiessupporting
confidence: 88%
“…Calcium-magnesium phosphate fertilizer can return alkaline substances to soils, resulting in increases in soil pH (Wu et al, 2008). Increases in soil pH because of swine manure applications may reflect the proton consuming ability of humic materials (Materechera and Mkhabela, 2002), and may have been due to the steady formation of organic material with functional groups during decomposition, such as carboxyl and phenolic groups, and by the low solubility of CaCO 3 (Steiner et al, 2007). However, the influence of mineral fertilizer on soil pH might be partially controlled by the soil characteristics and fertilizer properties.…”
Section: Effects Of Fertilizer Practices On Soil Propertiesmentioning
confidence: 99%
“…Because BC is generally low in inorganic N, it is usually applied in conjunction with mineral fertilizer (Chen et al, 2013). In fact, the combination of BC and mineral fertilizers has been shown to synergistically affect crop yield and growth in field studies (Atkinson et al, 2010;Lehmann et al, 2003;Steiner et al, 2007). In addition to the possible effects of BC on microorganisms described above, the combination of fertilizer and BC may also affect microorganisms in field studies (via direct mineral nutrient input or indirect crop effects).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, the long-term application of inorganic fertilizer reduced the soil nutrients availability in the evaluated urban agricultural soils (Table 2). This may be due to the transformation of available forms of nutrients into unavailable forms by the soil acidity, and the poor nutrients retention corresponding to the low organic matter content in inorganic fertilizer applied soils [49]. The supplement of readily available nutrients (i.e., inorganic fertilizers) for a long-term tends to reduce the organic matter content in soil which causes in reduction of cation exchangeable sites.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…The supplement of readily available nutrients (i.e., inorganic fertilizers) for a long-term tends to reduce the organic matter content in soil which causes in reduction of cation exchangeable sites. Therefore, soils ability to retain nutrients for plant growth get reduces and application of inorganic fertilizer in very short-terms is required to maintain the crop productivity [49]. Jiang et al [50] also reported a reduction of nutrient retention ability and crop production with respect to long-term application of inorganic fertilizers in winter wheat-maize rotation systems compare to the application of organic fertilizers.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%